Investigation on prevalence of xerophthalmia among patients of Brazilian ophthalmologists - Roncada, Maria José; Wilson, Donald; Lui Netto, Adamo; Berretta Netto, Olderigo; Kalil, Aldonia C. (Revista de Saúde Pública, 1978)
A study on prevalence of xerophthalmia was carried out in all States of Brazil, with the use of questionnaires forwarded to ophthalmologists. Results showed low prevalence of lesions considered more significant regarding xerophthalmia. As the study was retrospective in nature rates regarding population at risk could not be computed. However, data suggest that xerophthalmia is not a Public Health problem among us.